The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/w10101426
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelations between a Multi-Layered Coastal Aquifer, a Surface Reservoir (Fish Ponds), and the Sea

Abstract: This research examines the interrelations in a complex hydrogeological system, consisting of a multi-layered coastal aquifer, the sea, and a surface reservoir (fish ponds) and the importance of the specific connection between the aquifer and the sea. The paper combines offshore geophysical surveys (CHIRP) and on land TDEM (Time Domain Electro Magnetic), together with hydrological measurements and numerical simulation. The Quaternary aquifer at the southern Carmel plain is sub-divided into three units, a sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The CHIRP results indicate that seawater intrusion can take place, as observed in unit B (not in the underlying unit C and the overlaying unit A) at the southern part 75 m from sea, and not at the northern part. This was supported by numerical simulations, which showed that the difference in the offshore extension of the clay may delay SWI by years [18]. The hydraulic conductivity determined by field tests for units A, B and C were 30, 68 and 109 m/day, respectively, and the storativity in units B and C were 0.0001 and 0.0016, respectively [18].…”
Section: Hydrogeological Background Of the Study Areamentioning
confidence: 76%
See 3 more Smart Citations
“…The CHIRP results indicate that seawater intrusion can take place, as observed in unit B (not in the underlying unit C and the overlaying unit A) at the southern part 75 m from sea, and not at the northern part. This was supported by numerical simulations, which showed that the difference in the offshore extension of the clay may delay SWI by years [18]. The hydraulic conductivity determined by field tests for units A, B and C were 30, 68 and 109 m/day, respectively, and the storativity in units B and C were 0.0001 and 0.0016, respectively [18].…”
Section: Hydrogeological Background Of the Study Areamentioning
confidence: 76%
“…The study area includes two observation wells screened at unit B (T72 and T71-2), located 50 and 75 m from shore, respectively, and one pumping well (P211) opened both to unit B and to unit C, which is located 125 m from the sea (Figure 2). Due to pumping, water level in unit B (which is the subject of this study) is on the average 1.1 and 1.3 m lower than in the overlaying unit A and the underlying unit C, respectively [18]. Profiles in units A and C, 75 m from shore, show low and uniform EC values (5-6 mS/cm, like the natural conductivity in this area), while in unit B an interface was observed at a depth of 22 m, and salinity of bottom water reached 40 mS/cm [18].…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Tal et al [7] investigated the interrelationship between a multi-layered coastal aquifer at the southern Carmel plain in Israel, fish-ponds, and the sea using off-shore seismic surveying, on-land time-domain electromagnetic (TDEM) surveying, electrical conductivity (EC) profiles, hydrological field experiments, and groundwater levels. Using groundwater modelling, they showed that the exact location of the hydraulic connection between the confined aquifer unit and the sea (variable continuity of confining clay) played a significant role in the sensitivity of the aquifer unit to seawater intrusion.…”
Section: Impacts Of the Changing Environment On Coastal Groundwater Rmentioning
confidence: 99%